(x + 8)(x - 1) = (x + 1)²
So x² + 7x - 8 = x² + 2x + 1
5x = 9
x = 1.8
2006-11-05 11:14:11
·
answer #1
·
answered by Wal C 6
·
1⤊
0⤋
x=8+1 (-1)^2 so 1^(8+1)(x^2)= (1+1) =2
2006-11-05 11:20:06
·
answer #2
·
answered by jedi1josh 5
·
0⤊
0⤋
(x + 8)(x - 1) = (x + 1)(x + 1)
x^2 + 7x -8 = x^2 +2x + 1 (use foil)
7x -8 = 2x + 1 (the x^2's cancel out)
5x = 9 ( bring the 2x to the left side, and the 8 to the right side)
x = 9/5
2006-11-05 11:16:48
·
answer #3
·
answered by Ero T 1
·
0⤊
0⤋
(x+8)(x-1) = (x+1)^2
In order to get x by intself we need to make sure that you get rid of the parenthesis, so we multiply the 2 quantities on the left and foil out the quantity on the right, so you would get
x^2 + 7x - 8 = x^2 + 2x + 1
Then you get the x's all on one side and the constants on the others.
x^2 - x^2 + 7x - 2x = 1 + 8
Then you start simplifying,
5x = 9
Thus,
x = 9/5
2006-11-05 11:18:40
·
answer #4
·
answered by aplpie 3
·
0⤊
0⤋
Simplify both sides
x^2+7x-8=x^2+2x+1
sub x^2 from both sides
7x-8=2x+1
5x-8=1
5x=9
x=9/5 or 1 and 4/5 or 1.8
2006-11-05 11:13:56
·
answer #5
·
answered by mom 7
·
1⤊
0⤋
(x + 8)(x - 1) = (x + 1)^2
x^2 - x + 8x - 8 = (x + 1)(x + 1)
x^2 + 7x - 8 = x^2 + x + x + 1
x^2 + 7x - 8 = x^2 + 2x + 1
5x = 9
x = (9/5)
ANS : (9/5)
2006-11-05 11:56:28
·
answer #6
·
answered by Sherman81 6
·
0⤊
0⤋
(x+8)(x-1) = (x+1)(x+1) beginning
x^2+7x-8 + x^2+2x+1 distributive property/foil
7x-8=2x+1 subtract x^2
5x=9 subtract 2x and add 8
x=9/5 divide by 5
2006-11-05 11:48:32
·
answer #7
·
answered by osoboricuoso 2
·
0⤊
0⤋
If you perform the indicated operations - multiplication on the left and squaring on the right - then you'll get an equation with quadratics on both sides. The fortunate thing is that you'll have x^2 on both sides which you can subtract off leaving a linear equation which can be solved pretty handily.
2006-11-05 11:12:34
·
answer #8
·
answered by bag o' hot air 2
·
0⤊
0⤋
8x + 3(x + a million) = -x to unravel this challenge, we'd want to isolate x on the left part, as follows: a million. Distribute 3 in (x+a million), 3 (x+a million) = 3x + 3 rewrite the equation: 8x + 3x + 3 = -x 2. 8x + 3x = 11x, to be able to write down the eq. : 11x + 3 = -x 3. subtract -x from both part: 12x + 3 = 0 4. subtract 3 from both part: 12x = -3 5. Divide both part by technique of 12: x = -3/12 by technique of simplify, finally the answer is: x = -a million/4
2016-11-28 19:49:01
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
solved below
x(x-1)+8(x-1)=(x +1)^2, however,(x+1)^2=x^2+2x+1
x^2-x+8x-8=x^2 +2x +1 group like terms
x^2-x+8x-x^2-2x=1+8
5x=9
x=9/5
2006-11-05 11:22:29
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋